English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

The difference of the two numbers is 12. The product of the two numbers is 17.

Decimals included.

Any help would be awesome.

Thanks =)

2007-03-21 17:58:02 · 7 answers · asked by Hmmmmm 3 in Science & Mathematics Mathematics

7 answers

your equations will be
x - y = 12 and xy = 17
you get a quadratic equation

x^2 + 12x - 17= 0

use the quadratic formula so solve for x.

you'll get

x = - 6 + sqrt(19) or
x = -6 - sqrt(19) //answer

2007-03-21 18:16:53 · answer #1 · answered by 13angus13 3 · 0 0

Previous answer made a mistake as you can see by multiplying 19.5 X 7.5 = 146.25.
You need to set up 2 equations and then just use substitution:
X - Y = 12 and XY = 17. Work the substitution both ways and see which one is easier. (Just check the answers you get.)

I see that not many people can follow the quadratic formula through.
If X - Y = 12, then Y = X - 12
Substituting in XY = 17, we get X(X - 12) = 17
Multiplying we get x^2 - 12 X = 17 or X^2 - 12 X -17 = 0
a = 1, b= -12, c= -17
X = [-(-12) +/- Sqrt((-12)^2 - 4(1)(-17))]/2
X= [12 +/- Sqrt(144 - (4)(-17))]/2
X= [12 +/- Sqrt(144 + 68)]/2
X = [12 +/- Sqrt(212)]/2
X = [12 +/- 14.56...]/2
X= 6 +/- 7.28
X = 13.28 or -1.28
13.28 - 12 = Y or 1.28
X = 13.28, Y = 1.28
13.28 X 1.28 = 16.9984 which = 17 due to rounding.
13.28 - 1.28 = 12.

Therefore 13.28 and 1.28 are your numbers. Do each step carefully.

2007-03-22 01:13:17 · answer #2 · answered by smartprimate 3 · 0 0

Since the difference of the two numbers is 12, we know that x - y = 12.
Since the PRODUCT of the numbers is 17 we know x*y = 17.

x - y = 12
x = y + 12

So, x*y = 17
(y+12)*y = 17
y^2 + 12y = 17
y^2 + 12y - 17 = 0

From here you use the quadratic formula to get the solutions.

(By the way the solutions are 6 +/- sqrt(53).)

2007-03-22 01:12:03 · answer #3 · answered by polymac98 2 · 0 0

With x being the larger of the two numbers x,y then your solutions sets are (x,y):

A) (6+sqrt53, -6+sqrt53) or B) (6-sqrt53, -6-sqrt53)

-----------------
Proof for A
6+sqrt53 - (-6+sqrt53) = 12
(6+sqrt53) (-6+sqrt53) = -36 + 53 = 17

Proof for B
(6-sqrt53) - ( -6-sqrt53) = 12
(6-sqrt53) ( -6-sqrt53) = -36 + 53 = 17
-----------------
You will need to CAREFULLY use the quadratic formula on:

Y^2 + 12Y -17 = 0 Then x = 12 + Y

2007-03-22 01:56:18 · answer #4 · answered by answerING 6 · 0 0

x - y = 12
x*y= 17

x= 12+y
(12 + y)* y = 17
y^2 + 12y = 17
y^2 + 12y -17 = 0

Put that in the quadratic formula to get your answer.

2007-03-22 01:14:48 · answer #5 · answered by xaviar_onasis 5 · 0 0

x is one number
12-x is the other number
x(12-x) = 17
12x - x^2 = 17
x^2 -12x +17 =0
Quadratic formula or calculator
x = 10.36,1.64

2007-03-22 01:16:14 · answer #6 · answered by lizzie 3 · 0 0

x-y=12.....1
x=12+y.....2

x+y=17.....3

Put 2 into 3.
12+y+y=17
2y=15
y=7.5

x=12+7.5=19.5

So, the 2 numbers are 19.5 and 7.5.

I hope this helps. :)

2007-03-22 01:02:50 · answer #7 · answered by Juni Mccoy 3 · 0 0

fedest.com, questions and answers